Direct detection of Mycobacterium bovis by a dry loop-mediated isothermal amplification assay in cattle samples collected during routine abattoir examination in Malawi. (May 2023) - Kapalamula, Thoko Flav; Thapa, Jeewan; Hayashida, Kyoko; Chizimu, Joseph; Tanomsridachchai, Wimonrat; Nyenje, Mirriam Ethel; Mkakosya, Rajab; Nakajima, Chie; Suzuki, Yasuhiko
The lack of quick, accurate, and low-cost detection methods has hindered the active control strategies for bovine tuberculosis (bTB) in resource-limited countries with a high burden of disease. We developed a dry loop-mediated isothermal amplification (LAMP) assay for rapid and specific detection of Mycobacterium bovis, the principal causative agent of bTB, and evaluated the efficacy of the assay using suspected bTB samples collected during routine meat inspection at major regional abattoirs in Malawi. Template genomic DNA was extracted directly from the granulomatous bTB-like lesion (crude extracted DNA), as well as growth from the incubated mycobacterial growth indicator tubes (MGIT). Field results were visualized by the naked eye within 40 min following a color change of the amplified products. The sensitivity and specificity of the dry LAMP assay while using 152 DNA samples extracted from MGIT with confirmed M. bovis results were 98% and 88%, respectively. When 43 randomly selected crude DNA samples from lesions were used, the sensitivity and specificity of the dry LAMP assay were 100% and 75%, respectively. Our LAMP assay offers the potential to meet the demands for a low-cost and rapid field detection tool for bTB in resource-limited countries in which bTB is endemic.